2017
DOI: 10.5603/kp.a2017.0073
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of targeted temperature management after cardiac arrest in Polish intensive care units. What has changed in the last five years?

Abstract: A b s t r a c tBackground: Studies conducted up to 2010 indicate the underuse of targeted temperature management (TTM) in Poland. Aim:This study evaluated the current degree of TTM implementation in Polish intensive care units (ICUs) and analysed the implementation process since 2010. Methods:A telephone survey, conducted from December 2014 to July 2015, was carried out to determine the number of ICUs using TTM in patients after cardiac arrest. We collected data on the details and prevalence of TTM, and the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Krawczyk et al [17] emphasised the need for discussion and education when they reported that the TTM procedure in Polish ICUs is underused. The most common limitations include a lack of dedicated devices, logistical issues and a misunderstanding or misinterpretation of published evidence.…”
Section: -Specicitymentioning
confidence: 99%
“…Krawczyk et al [17] emphasised the need for discussion and education when they reported that the TTM procedure in Polish ICUs is underused. The most common limitations include a lack of dedicated devices, logistical issues and a misunderstanding or misinterpretation of published evidence.…”
Section: -Specicitymentioning
confidence: 99%
“…Results of a recent survey study showed that the prevalence of TTM in Poland is still low. Only about one-third of the intensive care units that responded to the survey use such a method [1].…”
Section: Introductionmentioning
confidence: 99%